Pembelajaran Inovatif Untuk Meningkatkan Guru Profesional: (Kajian Atas Peran Guru di MI Bustanul Ulum Campor Timur Ambunten Sumenep) - Siti Saroh Sunti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Professional teachers are a demand that must be met in order to improve the quality of the education process in schools. This means that teachers have an important role in education so that a teacher must have a high responsibility in improving the quality of student development. This paper presents a portrait of the professionalism of the teacher in MI Bustanul Ulum Ambunten illustrated through his four competencies, namely pedagogical, personality, social, and professional competencies. Teachers at MI Bustanul Ulum use innovative learning methods, namely: CTL Innovative Learning model (Contextual Teaching And Learning), Decision Making Innovative Learning Model. Group To Group Exchange Innovative Learning Model. By implementing an innovative learning model, it is expected to encourage MI teacher Bustanul Ulum to more quickly achieve the competencies that professional teachers must have so as to improve a teacher's professionalism. Keywords : Learning innovation and professional teachers